GENERATIONAL COLLABORATION STRATEGIES AND ORGANIZATIONAL SUCCESS: A CONCEPTUAL FRAMEWORK FOR CHINESE FAMILY BUSINESSES - Wu TianYang; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2024)
This research focuses on exploring the impact of cross-generational dynamics on strategic decision-making, implementation, and organizational performance within the context of family-owned businesses, particularly in the Chinese landscape. With the acceleration of social change and the resulting reduced generational gaps, there's a critical need to understand and manage the diverse needs, expectations, and leadership styles across generations within these enterprises. The study aims to investigate how cross-generational communication, leadership styles, human resource policies, and knowledge transfer influence strategic decision-making and organizational performance. Data is collected through questionnaires administered in family-owned businesses, focusing on the interplay between different generations and their impact on organizational success.